A Capital Maintenance Approach To Income Measurement. - Revsine, Lawrence (The Accounting Review, 1981)
ABSTRACT: This paper uses a simple example to isolate the underlying capital maintenance concepts that are associated with historical cost income and four widely discussed inflation accounting alternatives, The approach illustrates that each of these concepts conforms to Hicks' classical income definition and thus demonstrates why discussions of "true" inflation-adjusted income are oversimplified.